2015
DOI: 10.1111/ggi.12503
|View full text |Cite
|
Sign up to set email alerts
|

Who prefers to age in place? Cross‐sectional survey of middle‐aged people in Japan

Abstract: Sex, current living arrangement and geographic properties are correlated with changes in community-dwelling adults' preferences for residential relocation as physical function declines. It is necessary for municipal policymakers to understand these correlations in order to plan and develop effective community care systems. Geriatr Gerontol Int 2016; 16: 631-637.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Variables were included in the model if an association had a p -value < 0.20, following confirmation for multicollinearity. Because previous studies have reported an association with sex, age, household size, self-reported health, and experience with caring for family [9–11], these variables were included in the model, regardless of the current association. The goodness of fit for the model was confirmed using the Hosmer-Lemeshow test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables were included in the model if an association had a p -value < 0.20, following confirmation for multicollinearity. Because previous studies have reported an association with sex, age, household size, self-reported health, and experience with caring for family [9–11], these variables were included in the model, regardless of the current association. The goodness of fit for the model was confirmed using the Hosmer-Lemeshow test.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have focused on predictors of preferred care location [9–11]; however, few studies have contributed to promoting home care usage from 2025. A cross-sectional study analysed the predictors in community-dwelling individuals, including middle-aged adults (aged 40–79) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies relied on a single, abstract question, 21e25 and asked individuals about preferences for themselves in case of a hypothetical situation of disability without providing detailed information regarding the nature of disability. Effects on LTC preferences of increasing severity in a single dimension of disability were nevertheless reported by Guo et al 26 for BADLs, and by Matsumoto et al 27 for walking impairment. Some studies contrasted situations that differed simultaneously in several dimensions 20,28e31 and, therefore, could not disentangle the specific effects of multiple aspects included in disability profiles.…”
Section: Discussionmentioning
confidence: 94%
“…The high response rate in our survey was probably explained by a relationship of trust established over years in the local population with the conduct of the Lc65þ study. Previous research in this field was scarce and limited by small or convenience samples, 9,12,25,28,31,34,35 low participation, 16,27 conduct in population groups with specific cultural 20,28,30,31,36 or health 9,12,13,25,28,34 characteristics, survey methods likely to induce a selection bias in older populations (eg, data collected via the Internet), 15,16 failure to provide practical information to respondents regarding disability needs and social circumstances, or narrow focus on a small number of vignettes. In this context, 2 studies provided promising methodological innovations.…”
Section: Discussionmentioning
confidence: 99%